Léon Cordes écrivain et paysan. L’expérience du Paysan du Midi (fin des années 1940 - début des années 1950) : un billet d’humeur en occitan dans la presse agricole en français - Philippe Gardy (Lengas)
Léon Cordes (1913-1987) was a winegrower in the Minervois before the war, a horticulturalist in Lattes, near Montpellier, after the Liberation, an Occitan-speaking writer and a defender of the language that was his own. As a singer and theater performer, including on stage, Cordes was a popular educator, passionately seeking to forge links with a public that was still often Occitan-speaking by birth. Not surprisingly, in the early 1950s, he became involved with the new trade publication Le Paysan du Midi, founded and directed by Philippe Lamour (1903-1992), the father, among others, of that emblematic land development project, the Compagnie du Bas-Rhône. In 1952, under a pseudonym, he published a weekly humor column in Occitan, Sul pic de Miegjorn (Sur le coup de Midi), in Le Paysan du Midi, in which he commented on current events in vineyards, wine and much more, in a serious tone that was nonetheless full of critical verve. Cordes sought and found a tone in a language that was both deeply rooted and easy to understand, somewhere between theater, public intervention and complicity with his audience of winegrowers. This experience of "literacy" in an essentially oral language did not last, but it did reveal the difficult questions posed by an intervention in Occitan in a widely circulated French periodical.